2015
DOI: 10.2217/nnm.14.79
|View full text |Cite
|
Sign up to set email alerts
|

Triple Combination of Carbosilane Dendrimers, Tenofovir and Maraviroc as Potential Microbicide to Prevent HIV-1 Sexual Transmission

Abstract: The three-drug combination increases their antiviral potency and act synergistically as potential microbicide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 99 publications
1
24
0
Order By: Relevance
“…Similar results have been previously obtained for HIV-1 using a combination of these dendrimers with TFV and/or maraviroc. 25,[70][71][72] G2-NS16/TFV/RAL was the most potent combination regimen against HIV-2 isolates, which is consistent with the higher anti-HIV-2 potency of the G2-NS16 dendrimer when given alone relative to the other dendrimers.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Similar results have been previously obtained for HIV-1 using a combination of these dendrimers with TFV and/or maraviroc. 25,[70][71][72] G2-NS16/TFV/RAL was the most potent combination regimen against HIV-2 isolates, which is consistent with the higher anti-HIV-2 potency of the G2-NS16 dendrimer when given alone relative to the other dendrimers.…”
Section: Discussionmentioning
confidence: 58%
“…29,68,69 Therefore, to prevent these problems the ideal HIV microbicide should combine different classes of antiretroviral drugs acting in different targets with compounds that act in a non-specific way. 18 Here, we have shown that dendrimer/TFV/RAL combinations at a fixed 1:1:1 ratio have significant synergistic interactions against the primary R5-and X4-HIV-2 isolates. Similar results have been previously obtained for HIV-1 using a combination of these dendrimers with TFV and/or maraviroc.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…40 We previously demonstrated that G1-S4 and G2-S16 displayed a good safety profile and did not cause histopathological alterations in the vaginal epithelium in BALB/c mice and New Zealand White rabbits. 8,17,31 In particular, we have also demonstrated in female h-BLT mice that transmission of HIV-1 was efficiently blocked by vaginally applied G2-S16.…”
mentioning
confidence: 59%
“…Previously, we showed that both dendrimers did not induce vaginal irritation or inflammation in BALB/c mice and they were well tolerated for topical application. 8,17,31 Female BALB/c mice (20±2 g) that were 6-8 weeks old were housed at the CBMSO. Animal studies were conducted and approved by the CBMSO Institutional Animal Care and Use Committee (CEEA-CBMSO, Madrid, Spain).…”
Section: In Vivo Vaginal Challenge Assaymentioning
confidence: 99%